1994
DOI: 10.1128/mcb.14.3.1886
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated trans activation of DNA synthesis- and precursor-producing enzymes by polyomavirus large T antigen through interaction with the retinoblastoma protein.

Abstract: Previously constructed Swiss mouse 3T3 fibroblasts producing polyomavirus large T antigen after addition of dexamethasone were used to study the transcriptional activation by the viral protein of five genes coding for enzymes involved in DNA synthesis and precursor production, namely, dihydrofolate reductase, thymidine kinase, thymidylate synthase, DNA polymerase a, and proliferating-cell nuclear antigen. It was found that all these genes, whose expression is stimulated at the G1/S boundary of the cell cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 40 publications
3
43
0
Order By: Relevance
“…This suggested that 5-FU might be more efficiently activated to FdUMP in RB-deficient cells than in RB-proficient cells. Consistent with this concept, the promoters of two genes encoding enzymes involved in 5-FU metabolism to FdUMP, thymidine kinase and RNR (Longley et al, 2003), are regulated by the RB/E2F axis (Mudrak et al, 1994;Angus et al, 2002). Indeed, expression of the RNR small subunit (RNR2) was significantly elevated following acute RB loss in primary MAFs (Figure 7e).…”
Section: Disparate Rb-dependent Checkpoint Responses Of Primary and Isupporting
confidence: 61%
See 1 more Smart Citation
“…This suggested that 5-FU might be more efficiently activated to FdUMP in RB-deficient cells than in RB-proficient cells. Consistent with this concept, the promoters of two genes encoding enzymes involved in 5-FU metabolism to FdUMP, thymidine kinase and RNR (Longley et al, 2003), are regulated by the RB/E2F axis (Mudrak et al, 1994;Angus et al, 2002). Indeed, expression of the RNR small subunit (RNR2) was significantly elevated following acute RB loss in primary MAFs (Figure 7e).…”
Section: Disparate Rb-dependent Checkpoint Responses Of Primary and Isupporting
confidence: 61%
“…Interestingly, we detected increased formation of the inactive ternary complex in RBdeficient cells exposed to 5-FU. We speculate that this was due to the RB/E2F-targets RNR and thymidylate kinase (TK) that are elevated in RB-deficient cells (Ogris et al, 1993;Mudrak et al, 1994;DeGregori et al, 1995;Angus et al, 2002). Analysis of upstream DNA damage checkpoint signaling revealed similar kinetics of activation of p53 by 5-FU in both RB-proficient and RB-deficient cells.…”
Section: Discussionmentioning
confidence: 88%
“…Stable REF52 lines, inducibly expressing wild type PyLT (REF52-LT8) and mutated PyLT (REF52-LTRB 7 12) were generated by calcium phosphate cotransfection of the plasmid pSV2neo and pMMTV-PyLT or pMMTV-PyLTmut respectively (Ogris et al, 1992;Mudrak et al, 1994), and subsequent selection in the presence of Geneticin (600 mg/ml of medium). Time determination of population doubling (PDL) was done as described previously (Otto et al, 1989).…”
Section: Cell Culturementioning
confidence: 99%
“…LT is a nuclear phosphoprotein that induces cellular DNA synthesis and cell division, is responsible for immortalizing cells, and is necessary for viral DNA synthesis (Francke and Eckhart, 1973;Schlegel and Benjamin, 1978;Rassoulzadegan et al, 1983). LT associates with pRB and this association is necessary for the induction of cellular DNA synthesis and immortalization of primary cells (Dyson et al, 1990;Larose et al, 1991;Freund et al, 1992Freund et al, , 1994Mudrak et al, 1994). Several other DNA tumor viruses, including SV40, adenovirus, and human papilloma virus, encode proteins that associate with and inactivate both p53 and pRB (Sarnow et al, 1982;DeCaprio et al, 1988;Whyte et al, 1988;Werness et al, 1990).…”
Section: Introductionmentioning
confidence: 99%